The Pandemic as Pedagogical Provender: A Response to “The Global Pandemic as Learning Opportunities about the World: Extending School Curriculum” - Mary Beth Schaefer (Middle Grades Review, 2020)
In this article, Mary Beth Schaefer responds to Bogum Yoon’s essay, “The Global Pandemic as Learning Opportunities about the World: Extending School Curriculum,” published in Middle Grades Review (2020). Schaefer situates Yoon’s ideas for integrative curriculum within core philosophies of the middle grades movement and challenges the field to take up Yoon’s suggestions to engage all middle grades students in integrative global investigations of the pandemic; furthermore, Schaefer suggests that educators might use these investigations as a way to initiate conversations with middle grades students and educators in other countries to facilitate international discourses and global perspectives.
Keywords: middle school; middle grades; early adolescence; young adolescents; international education; global education